PENGARUH WORK LIFE BALANCE, BUDAYA ORGANISASI, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI - Muhammad Nuskan Abdi; Chalimah Chalimah (Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to examine and analyze the effect of work life balance, organizational culture, and job satisfaction on organizational commitment. The main theory used as a reference is the theory of expectations. Based on the type, the authors use a Correlational research method with a quantitative approach. In this study, data collection was carried out using a questionnaire. As for determining the sample, the authors used a random sampling technique of 41 people. The conclusions of this study are (1) work life balance positive but not significant  influence organizational commitment, (2) organizational culture positive significantly influence on organizational commitment, (3) Job satisfaction is positive significantly influence on organizational commitment.